Surface ultrastructure of third-instar Megaselia scalaris (Diptera: Phoridae) - Sukontason K.L. (2014)
We describe some ultrastructure of the third-instar Megaselia scalaris (Diptera: Phoridae) using scanning electron microscopy, with the cephalic segment, anterior spiracle and posterior spiracle being emphasized. This study provides the taxonomic information of this larval species, which may be useful to differentiate from other closelyrelated species.